The Effect Of Make A Match Type Cooperative Learning Model On Ips Outcomes Of Class Iv Grade Sd Inpres Mangasa I Rappocini District Makassar - Asriani Asis; Widya Karmila Sari Achmad; Suarlin Suarlin (Program Studi PGSD FIP UNM, 2021)
This research 1) how is the description of implementation of match model learning strategies of fourth grade students at SD Inpres Mangasa I kecamatan Rappocini Makassar 2) How is the result of IPS (social science) learning of fourth grade students at SD 3) Is there any influence of match model learning model towards the result of students' learning in IPS subject at SD. The objectives of this researh are: 1) the description of implementation of match model learning strategies of fourth grade students at SD Inpres Mangasa I kecamatan Rappocini Makassar 2) the result of IPS (social science) learning of fourth grade students at SD 3) The influence of make a match learning model towards the result of students' learning in IPS subject at SD. The research approach uses quantitative with quasi eksperiment research type. The independent variable of this research is the influence of make a match learning model while dependent variable is the result of learning at IPS subject in the topic of living environment and types of economy. The population of this research is fourt grade students at SD Inpres Mangasa I Kecamatan Rappocini Makassar, and the sample is students of class IV A which consists of 24 students at control class and students of class IV B which consists of 24 students at experiment class. The design of this research is nonequivalent control group. The technique of sampling of this research is simple random sampling. While the technique of collecting data in this research is by giving test which is divided into pretest and posttest observasion and documentation. The normality test uses kolomogrov smirnov normality test. The hypothetical test uses T test of Independent Sample with the data from control class and experimental class. The result shows that there is significant influence. The research conclueded that there is a significant influence of make a match learning model toward the result of students’ learning in IPS class fourth at SD Inpres Mangasa I Kecamatan Rappocini Makassar.